Utilization of Gracilaria sp. liquid for bioethanol production - Nur Zatul 'Iffah Zakaria (School of Bioprocess Engineering, Universiti Malaysia Perlis, 2015)
The present study was aimed at utilizing Gracilaria sp. liquid either as ethanol feedstock or supplement in fermentation media. To achieve this aim, Saccharomyces cerevisiae was used as a benchmark. Some locally isolated strains have been screened, isolated and tested their efficacy in fermenting Gracilaria sp. liquid to produce ethanol. Prior to fermentation, the liquid was pre-treated using thermal dilute sulphuric acid hydrolysis in sequence to increase reducing sugar concentration and its conditions were statistically optimized by using Response Surface Methodology (RSM) method.